2012
DOI: 10.1177/1356389012452052
|View full text |Cite
|
Sign up to set email alerts
|

Applications of contribution analysis to outcome planning and impact evaluation

Abstract: Contribution analysis is a structured approach to theory-based impact evaluation originally developed in Canada in the context of Results-Based Management (RBM) although there have been few examples of contribution analysis in practice since Mayne's original paper (2001). We argue that contribution analysis adds value to other theory-based evaluation approaches by providing a more structured and rigorous approach to participatory evaluation planning, data analysis and reporting. It can be applied in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 18 publications
(18 reference statements)
0
37
0
1
Order By: Relevance
“…This collaboration is one of the more valued aspects of the contribution analysis methodology (Wimbush, Montague and Mulherin, 2012). Coupled with robust evidencegathering, we have found that this reflective approach to evaluation can also generate new theoretical understandings of the change process.…”
Section: Methodsmentioning
confidence: 99%
“…This collaboration is one of the more valued aspects of the contribution analysis methodology (Wimbush, Montague and Mulherin, 2012). Coupled with robust evidencegathering, we have found that this reflective approach to evaluation can also generate new theoretical understandings of the change process.…”
Section: Methodsmentioning
confidence: 99%
“…In such situations, CA can provide an attractive alternative evaluation approach as it does not require the use of counterfactual-based evaluation designs nor promises unequivocal understandings of the direct cause-and-eff ect relationships between an intervention and the observed results ( Befani & Mayne, 2014 ;Dybdal, Nielsen, Lemire, & Ramboll Management Consulting, 2011 ;Mayne, 2008 ). By seeking to provide evidence by which one can "reasonably" assert the contribution of an intervention to observed results, it relies on tests of alternative explanations to act as substitute candidates in place of counterfactuals to determine the plausibility of a proposed theory of change and the signifi cance and, accordingly, the infl uence of the intervention in producing observed changes ( Befani & Mayne, 2014 ;Lemire, 2010 ;Wimbush, Montague, & Mulherin, 2012 ).…”
Section: What Is Ca and What Is Its Underlying Approach To Causality?mentioning
confidence: 99%
“…Due to these advantages, CA has been increasingly applied in areas such as the fi eld of international development evaluation where intended, and actual causal relationships between interventions and results are heavily dependent on the situational context, including the considerable amount of time that may be required before results are observed ( Kotvojs & Shrimpton, 2007 ;Noltze, Gaisbauer, Schwedersky, & Krapp, 2014 ). Other examples of CA in practice include various government-driven interventions with complicated or complex program characteristics (including causal chains) and undefi ned time frames for expected results ( Biggs, Farrell, Lawrence, & Johnson, 2014 ;Delahais & Toulemonde, 2012 ;Wimbush, Montague, & Mulherin, 2012 ). With increasing requirements from government and funding agencies to move away from evaluations based solely on implementation performance metrics and toward measurable impacts, CA is intended to provide evaluators with the ability to conclude with a reasonable degree of confi dence that an intervention is contributing to observed results and to provide an evidence-based justifi cation of how this is probably occurring ( Kotvojs & Shrimpton, 2007 ).…”
Section: What Is Ca and What Is Its Underlying Approach To Causality?mentioning
confidence: 99%
See 1 more Smart Citation
“…Using CA relies on ensuring that the ToC is sufficiently complex to reflect the many intricacies that may arise later in the evaluation process while avoiding overcomplicating the framework to the point where the evaluation becomes unfeasible (Delahais & Toulemonde, ). Building a strong ToC requires ensuring that alternate explanations have been properly identified (Delahais & Toulemonde, ; Mayne, ; Wimbush, Montague, & Mulherin, ). In their experience, Delahais and Toulemonde () maintain that researchers pay greater attention to drawing causal links between the boxes in the ToC than to exploring alternative explanations.…”
Section: Recommendations For Toc Developmentmentioning
confidence: 99%